Telemedicine Service Quality, Customer Satisfaction and Continual Usage during the Covid-19 Pandemic - Miranti Anggorodhiyu Lokantari; Robert Kristaung (Budapest International Research and Critics University, 2022)
The use of telemedicine through health applications has increased since the COVID-19 pandemic. It is important to understand more deeply about people's experiences using telemedicine and explore the hospitality component of telemedicine. Objective: This study aims to determine the effect of telemedicine service quality on customer satisfaction and continual usage during the COVID-19 pandemic. Research Method: Data analysis using PLS-SEM technique with SmartPLS application. First, the measurement model test was conducted by testing the validity and construct reliability of each indicator, then testing the structural model to determine the relationship between the variables in the research model. Data was collected by distributing a 5-point Likert scale questionnaire, obtained 400 respondents who had done telemedicine with health applications at least once during the pandemic. Research results: system quality and interaction quality shape telemedicine service quality, telemedicine service quality has a positive effect on customer satisfaction and continual usage, customer satisfaction has a positive effect on continual usage. In addition, it was found that telemedicine service quality fully mediates in influencing system quality and interaction quality on customer satisfaction., customer satisfaction fully mediates in influencing telemedicine service quality on continual usage of health applications. Managerial Implications: as an evaluation material for health applications in maintaining and increasing customer satisfaction and continual usage.